The Influence Of Competitive Advantage, Entrepreneurial Orientation And Product Innovation On Business Success - Maulana, Rian; Danial, R Deni Muhammad; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine the influence of competitive advantage, entrepreneurial orientation, and product innovation on the business success of snack food MSMEs in Sukabumi City. The phenomenon observed is the importance of innovation and competitive advantage in facing intense business competition. The problem identified is that it is unclear how much each of these factors contributes to the success of MSME businesses. This study used quantitative method with descriptive approach and associative analysis. Data were collected through questionnaires distributed to 67 snack food MSMEs in Sukabumi City. Validity and reliability of the instruments were tested using SPSS, and multiple linear regression analysis was used to test the research hypotheses. The results showed that competitive advantage had a positive and significant influence on business success with a significance value of 0.022. In contrast, entrepreneurial orientation and product innovation do not have a significant influence on business success, with a significance value of 0.118 and 0.695, respectively. It is concluded that competitive advantage is a key factor in determining business success of snack food MSMEs in Sukabumi, while entrepreneurial orientation and product innovation have no significant influence. Therefore, it is recommended that MSMEs in Sukabumi should focus more on developing competitive advantage to achieve better business success.